Improving PPKN Learning Outcomes through Class IV Discovery Learning Learning Model SD Negeri 1 Adisana - Nur Hasanah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
Improving PPKn Learning Outcomes through Class IV Discovery Learning Model SD Negeri 1 Adisana is a research conducted to improve learning outcomes of PPKn Class IV SD Negeri 1 Adisana, material about environmental impacts that are not maintained, this is done because the learning outcomes of students' formative test scores are still low. The research was carried out by applying the discoveru learning model with the group discussion method in PPKn lessons. The study was conducted in 3 cycles, because researchers expect student learning outcomes to increase by up to 90 percent. The research was carried out with the help of colleagues as observers. Based on the results of reflection in cycle I student learning outcomes increased to 74.1 percent, where in the pre-cycle only 37 percent of students completed. Then in cycle 2 it increased to 96.3 percent then in cycle 3 it increased to 100 percent. Based on these results, the application of the discovery learning model improves the learning outcomes of fourth grade students in the PPKn subject matter that is not maintained environmental impact.